RAYLEIGH WAVE TOMOGRAPHY USING AMBIENT NOISE DATA IN GEOTHERMAL FIELD: A CASE STUDY - NAPITUPULU (NIM: 12313041), RAYMOND
Recently, advances in Geophysical methods have introduced some new techniques for assessing subsurface structure. In general, seismic is the most popular method in earth’s interior imaging. Currently, it has been developed into several kinds, one of which is seismic ambient noise tomography (ANT). In contrast with conventional seismic method which noise disrupt data quality, but noise in ANT method contain useful information to image the subsurface structure. Moreover, ANT is not depend on the active sources location such as earthquake or other explosive sources. Therefore, it can cover wide area based on the receiver station deployment. In geothermal field, it can be an effective method to describe the condition of shallow subsurface structure relatively. Data used in this study is result of seismic recording during 6 months using 10 short period seismometers, with 2 Hz dominant frequency. In general, phase of data processing in ANT divided into four main phase: (1) Single station processing, (2) Pair station processing, (3) Dispersion curve extraction, (4) Group velocity tomography. From data recording, each station pairs are cross-correlated with 0.1 – 5 s filtering. Cross-correlation function that is resulted associate with Green’s function which is processed to obtain the dispersion curve further. The clear dispersion curves have been selected to produce Rayleigh wave group velocity in the period range between 1.5 and 5 s, as the final result of this study. From the group velocity map, the existence of major fault at NW-SE direction can be identified in the study area which is marked with boundary between low and high velocity anomaly. Moreover, in the middle of the study area, low anomaly is identified which probably is representation of rock layer with high permeability. This result positively correlate with geology setting and another geophysics method.